Cross-validation of a self-report scale for postoperative pain in school-aged children - Suwannee Suraseranivongse (2018)
The present study cross-validated self-report pain scales: Verbal Rating Scale (VRS), Facial Expression Scale (FACES), Color Analogue Scale (CAS) and Poker Chip Tool (PCT) in Thai children aged 5-12 years. The concordance with observational measure, Children's Hospital of Eastern Ontario Pain Scale (CHEOPS) was also tested. Among 100 students, test-retest reliability of all self-report measures was moderate to good (K = 0.501-0.712) and only FACES yielded acceptable face validity (IC > 0.5). Validation in 87 patients, all scales showed construct and concurrent validity. FACES was the most preferred scale. Agreement of self-report measures and CHEOPS was better in the age group 5-8 years (K = 0.417-0.826) than 9-12 years (K = 0.231-0.529). In conclusion, FACES is a valid, reliable and practical tool. Self-report measures are more in concordance with CHEOPS in the younger age group.